Desain Strategi Pembelajaran Bahasa Arab Di MI - Khotijah Khotijah (Institut Agama Islam Negeri Metro, 2018)
There are two crucial things essence in the learning proses. They are teachers and students. The teachers are the main actors in teaching, and students are main actors in learning. Basically learning is a process of change, from not knowing to know, less good to be good trough interaction between individuals and the environment. In school learning proses is a continous series of activities, planed, integrated which gives overall characteristics in the learning process. Skill and ways of teaching teachers in managing the learning process is called learning strategies. A teacher must design learning with the right strategy so that the material presented to students can be delivered maximally and please them. Whether or not the use of a particular strategy in learning depends on the goals, material, character of learners and teachers. So there is no specific strategy that is best and suitable for all learning situations and conditions. But it is the strategies that fit the learning needs. The characteristics of primary school children should be a special consideration in designing of learning strategies.